The rural energy sector and the environment: a case study of West Gonja District, Ghana - Mubita, Simangolwa Mukelabai (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the award of the Degree of Master of Science in Development Planning and Management.